2018
DOI: 10.1148/rg.2018170173
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Electronic Cleansing for Single- and Dual-Energy CT Colonography

Abstract: Electronic cleansing (EC) is used for computational removal of residual feces and fluid tagged with an orally administered contrast agent on CT colonographic images to improve the visibility of polyps during virtual endoscopic "fly-through" reading. A recent trend in CT colonography is to perform a low-dose CT scanning protocol with the patient having undergone reduced-or noncathartic bowel preparation. Although several EC schemes exist, they have been developed for use with cathartic bowel preparation and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…However, the potential usefulness of this software application is still limited by a number of artefacts that can affect the colonic evaluation and interpretation, as well as the size measurement of colonic lesions that are submerged under tagged faecal residue. Future strategies to further reduce EC-related pitfalls and artefacts may include EC schemes that are based on the material decomposition capability of dual-energy CT [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…However, the potential usefulness of this software application is still limited by a number of artefacts that can affect the colonic evaluation and interpretation, as well as the size measurement of colonic lesions that are submerged under tagged faecal residue. Future strategies to further reduce EC-related pitfalls and artefacts may include EC schemes that are based on the material decomposition capability of dual-energy CT [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Those CT volumes were separated into three groups (three groups consist of 2, 2 and 3 CT volumes, respectively) for cross-validation. 6…”
Section: Methodsmentioning
confidence: 99%
“…Most intestinal segmentation methods 8,9 are applied only for the large intestines with assumption of fecal tagging by contrast agents. Virtual cleansing of feces 5,6 mentioned in the previous paragraph is also assuming fecal tagging. In summary, compared to segmentation of large intestines with fecal tagging, segmentation for ileus patients are difficult due to 1) low contrast between fluid and intestinal wall and 2) long and winding shape of the small intestines.…”
Section: Introductionmentioning
confidence: 99%
“…In the bowel, CT colonography computer-aided polyp detection was a hot topic in abdominal CT image analysis over a decade ago. Recent progress with deep learning has been limited but studies have reported improved electronic bowel cleansing, and higher sensitivities and lower false-positive rates for precancerous colonic polyp detection [187], [190]. Deep learning using persistent homology has recently shown success for small bowel segmentation on CT [191].…”
Section: Deep Learning In Abdominal Imagingmentioning
confidence: 99%